2013
DOI: 10.1186/1471-244x-13-75
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sunlight exposure on interleukin-6 levels in depressive and non-depressive subjects

Abstract: BackgroundThe objective of this epidemiological study was to evaluate the effect of length of sunlight exposure on interleukin 6 (IL-6) levels in depressive and non-depressive subjects.MethodsThis was a cross-sectional study with 154 subjects (54 males, mean age: 43.5 ± 12.8 years) who were living in a rural area in south Brazil. Chronobiological and light parameters were assessed using the Munich Chronotype Questionnaire. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index. Depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Levels of IL-6 were lower in the low light exposure depressive group compared to the high light exposure to depressive groups. The hypothesis that impairment of the suprachiasmatic nucleus leads to different IL-6 levels in the depressive subjects was established in this study, and that MDD could benefit from sunlight exposure [122].…”
Section: Light Therapymentioning
confidence: 83%
See 1 more Smart Citation
“…Levels of IL-6 were lower in the low light exposure depressive group compared to the high light exposure to depressive groups. The hypothesis that impairment of the suprachiasmatic nucleus leads to different IL-6 levels in the depressive subjects was established in this study, and that MDD could benefit from sunlight exposure [122].…”
Section: Light Therapymentioning
confidence: 83%
“…A direct relationship between sunlight exposure and plasma IL-6 level changes in a study where the effects of sunlight exposure on plasma IL-6 in depressive and non-depressive subjects were investigated [122]. IL-6 levels were not affected by exposure to various different intensities of light in non-depressed subjects.…”
Section: Light Therapymentioning
confidence: 98%
“…For instance, Tsai et al (2011) observed sunlight-related variation of striatal dopamine receptor availability. Other limited data reported seasonal variations in serum BDNF concentrations (Molendijk et al, 2012) or changes in interleukin-6 levels depending on the sunlight exposure (Levandovski et al, 2013). Finally, it should be mentioned the role of vitamin D in depression (Howland, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Both increased sun exposure (Dhar and Lambert, 2013;John et al, 2004;Kent et al, 2013a;Kent et al, 2013b;Levandovski et al, 2013) and the consumption of green vegetables (Block et al, 1992;Ferruzzi and Blakeslee, 2007;van't Veer et al, 2000) are correlated with better overall health outcomes in a variety of diseases of aging. These benefits are commonly attributed to an increase in vitamin D from sunlight exposure and consumption of antioxidants from green vegetables.…”
Section: Resultsmentioning
confidence: 99%